A diet-wide Mendelian randomization analysis: causal effects of dietary habits on type 2 diabetes - Xiao, Rui; Dong, Li; Xie, Bo; Liu, Beizhong (Frontiers in Nutrition, 2024)
Traditional clinical studies have indicated a link between certain food intakes and type 2 diabetes (T2D), but the causal relationships between different dietary habits and T2D remain unknown. Using Mendelian randomization (MR) approaches, we investigated the potential causal association between dietary habits and T2D risk. We collected publicly available genome-wide association studies' summary statistics for 18 dietary habits from the UK Biobank and T2D data from the DIAbetes Genetics Replication And Meta-analysis (DIAGRAM) consortium. We applied the inverse variance weighted (IVW) method, supplemented with the MR-Egger method, weighted median method (WMM), simple method, weighted mode, MR-Egger regression, and the MR pleiotropy residual sum and outlier test to determine whether a particular diet was causal for T2D.Reliable and robust MR estimates demonstrated that poultry intake has a causal effect on a higher risk of T2D (IVW: